AB0155 Anti-VCA and EBNA1 antibodies are produced in the rheumatoid synovium in the presence of ectopic lymphoid structures and correlate with ACPA production. (23rd January 2014) - Croia, C.; Bombardieri, M.; Serafini, B.; Humby, F.; Migliorini, P.; Aloisi, F.; Pitzalis, C.
Abstract : Background: Ectopic lymphoid structures (ELS) are preferential sites for Epstein-Barr virus (EBV) latency and reactivation in the brain of multiple sclerosis (1) and are functional sites of autoreactive B cell activation in the synovial tissue of rheumatoid arthritis (RA) patients (2) leading to the in situ production of anti-citrullinated protein/peptide antibodies (ACPA). However, it is unknown whether ELS are responsible for the generation of antibodies against native and/or post-translationally modified EBV proteins. Objectives: In this work we aimed: 1) To investigate the presence of anti-VCA, anti-EBNA1, anti-EA and ACPA antibodies in the serum vs synovial fluid (SF) of RA patients; 2) To provide in vivo evidence of the synovial production of antibodies against unmodified and citrullinated EBV-proteins (3) in the HuRA/SCID chimeric model; 3) To investigate whether EBV-infected synovial plasma cells produce ACPA. Methods: Anti-EBNA1, anti-VCA, anti-EA and ACPA IgG were measured in paired serum and SF from RA and OA patients. The local production of unmodified and citrullinated (VCP1 and VCP2) anti-EBV antibodies (3) was investigated by screening the serum of 30 SCID mice transplanted with ELS+ vs ELS- RA synovium. Finally, sequential double immunofluorescence for biotinylated citrullinated fibrinogen (BCf), BFRF1 (EBV lytic antigen) and CD138 was used to detect EBV reactivation in ACPA-producing synovial plasma cells. Results: Serum and SF levels of anti-EBNA1, anti-VCA and ACPA IgG were significantly correlated. Sera of SCID mice transplanted with ELS+ (but not ELS-) RA synovia displayed high levels of human IgG ACPA, anti-EBNA1 and anti-VCA but not anti-EA antibodies. Interestingly, a proportion of SCID mice sera displaying high reactivity against anti-CCP and anti-EBNA1 antibodies were also found positive for anti-VCP1 and VCP2. Finally, in ELS+ RA synovia a subset of locally differentiated ACPA+ plasma cells surrounding ectopic germinal centres displayed EBV lytic infection as detected by reactivity for BFRF1. Conclusions: Here we showed that antibodies against unmodified and citrullinated EBV antigens are locally produced in the RA synovium in the presence of ELS and are closely associated with in situ ACPA production. Evidence of ACPA+ plasma cells showing lytic EBV infection strongly supports an important role for EBV in the activation and differentiation of autoreactive B cells within the RA synovium. References: Serafini B, Rosicarelli B, Franciotta D, Magliozzi R, Reynolds R, Cinque P, Andreoni L, Trivedi P, Salvetti M, Faggioni A, Aloisi F. Dysregulated Epstein-Barr virus infection in the multiple sclerosis brain. J Exp Med. 2007 Nov 26;204(12):2899-912. Humby F, Bombardieri M, Manzo A, Kelly S, Blades MC, Kirkham B, Spencer J, Pitzalis C. Ectopic lymphoid structures support ongoing production of class-switched autoantibodies in rheumatoid synovium. PLoS Med. 2009 Jan 13;6(1):e1 Pratesi F, Tommasi C, Anzilotti C, Chimenti D, Migliorini P. Deiminated Epstein-Barr virus nuclear antigen 1 is a target of anti-citrullinated protein antibodies in rheumatoid arthritis. Arthritis Rheum. 2006 Mar;54(3):733-41. Disclosure of Interest: None Declared